India-Bhutan economic relations - Nisha Taneja; Samridhi Bimal; Taher Nadeem; Riya Roy (Indian Council for Research on International Economic Relations (ICRIER), 2019)
The year 2018 was a milestone year for India-Bhutan relationship as the countries celebrated the accomplishments of the last fifty years of time-tested and special ties. The mutually beneficial economic ties have been the centre-piece of India-Bhutan relationship. India is Bhutan's largest export market, the biggest source of its imports and one of the top foreign investors in the country. India also provides Bhutan transit facility through its territory to access sea ports for trading with rest of the world. Cooperation in hydropower projects is one of the most significant examples of win-win cooperation between India and Bhutan. These projects are a reliable source of inexpensive and clean electricity to India, a major contributor towards Bhutanese GDP and strengthening India-Bhutan economic integration. Bhutan has been pivotal to two of India's major foreign policies - the "Neighborhood First Policy" and the "Act-East Policy". After coming into power in 2014, the Narendra Modi-led BJP government has laid special emphasis on India's neighborhood as well as its relations with Bhutan, which have mostly been tension free. It is in this context that this paper examines the bilateral economic relationship between India and Bhutan. The paper analyses the bilateral trade patterns of India and Bhutan along with their maximum additional potential. The paper discusses Bhutan's transit arrangement with India, the importance of connectivity between the two countries, the flow of Indian investment in Bhutan and the cooperation between India and Bhutan in hydroelectric power projects. The paper discusses several constraints to trade and transit infrastructure. It also discusses issues related to cross-border trade in electricity. The paper concludes by making policy recommendations that could enhance the economic relationship between India and Bhutan.
Keywords: F10; F13; F15; F50; P45; 330; India-Bhutan; Bilateral Trade; Bilateral Investment; Trade in Electricity; Connectivity